First Stage Larvae of Meloidae (triungulinus) as enemies of the honey bee in Greece - Λιάκος Β.; Πασάλογλου - Κατράλη Μ. (Journal of the Hellenic Veterinary Medical Society, 2019)
First stage larvae of Meloe proscarabaeus (Meloidae - Coleoptera) a honey bee pest, are reported for the first time in Greece. These species one of the less harmful of the family meloidae, do not cause serius damages on bees in Greece.